IMPLIKASI BERPIKIR KOMPUTASIONAL BAGI PENINGKATAN PEMECAHAN MASALAH MATEMATIS SISWA MI/SD - Nanik ulfa; Isna Nurul Inayati (Universitas Islam Raden Rahmat Malang, 2026)
This study aims to examine the critical role of computational thinking in enhancing mathematical problem-solving skills among students in Madrasah Ibtidaiyah (MI) and elementary schools. Using a literature review approach, this research analyzes various scholarly sources that discuss the relationship between key components of computational thinkingsu ch as decomposition, pattern recognition, abstraction, and algorithmic design and the development of students’ numeracy and logical reasoning abilities. The findings reveal that integrating computational thinking into mathematics instruction enables students to understand problems more systematically, select appropriate solution strategies, and foster creativity in generating solutions. Beyond its cognitive benefits, this approach also supports the growth of essential character traits such as independence, persistence, and collaboration. However, the literature also highlights variations in students’ mastery of computational thinking skills and the challenges teachers face in implementing them, underscoring the need for innovative instructional practices and curriculum adjustments. Overall, the study affirms the importance of integrating computational thinking into elementary mathematics education as a foundational step toward strengthening mathematical literacy and preparing students for the demands of the digital era.